Vitiligo patients from India (Mumbai) show differences in clinical, demographic and autoantibody profiles compared to patients in western countries. (28th November 2011) - Pradhan, V.; Patwardhan, M.; Thakkar, V.; Kharkar, V.; Khopkar, U.; Ghosh, K.; Weetman, A.P.; Gawkrodger, D.J.; Kemp, E.H.
Abstract Background Vitiligo is a common, idiopathic skin disorder characterized by depigmented skin due to the loss of cutaneous melanocytes. Several studies have reported the clinical and demographic characteristics of Indian vitiligo patients, however, none has characterized their antibody profiles. Objective To establish the clinical, demographic and serological details of a population of vitiligo patients from Mumbai, India, and to evaluate the data for any associations between clinical presentations and the occurrence of antibody responses. Methods Vitiligo patients (n = 79) were recruited to the study and their clinical and demographic details recorded. Serum antibodies, including those against melanocyte‐specific antigens, thyroid antigens and keratinocytes, were evaluated. Results The prevalence of vitiligo was independent of sex, and non‐segmental vitiligo was the most common form of the disease occurring in 65% of the patients. Patients with segmental vitiligo (mean age = 14.4 ± 4.6 years) presented at a younger age than those with non‐segmental disease (mean age = 32.5 ± 17.8 years). Personal and family histories of other autoimmune diseases occurred in 3% and 8% of patients, respectively. Antibodies were detected against tyrosinase, tyrosine hydroxylase, thyroid peroxidase, thyroglobulin and keratinocytes at frequencies of 11%, 22%, 18%, 24% and 27%, respectively. Overall, antibodies were more common in patients with non‐segmental vitiligo (50–67%) than in those with segmental disease (0–17%), and were detected more frequently in patients with shorter disease durations (<10 years). Conclusion Our study provides novel information relative to the clinical details, demographic features and serological parameters of a population of vitiligo patients from Mumbai, India. Important distinctions from similar surveys conducted in European patients were evident such as an infrequency of family history, a low prevalence of clinical autoimmune disease, and an absence of particular antibody specificities. These differences may have a bearing on the pathogenesis and course of the disease in Indian patients.